Accuracy of duplex ultrasound in peripheral artery disease: a systematic review and meta-analysis - Silfayner Victor Mathias Dias; Ronald Luiz Gomes Flumignan; Nelson Carvas Junior; Wagner Iared (Jornal Vascular Brasileiro)
Abstract Lower limb peripheral artery disease (PAD) is highly prevalent. Current guidelines recommend duplex ultrasound (DUS) with spectral analysis for diagnosis. This systematic review and meta-analysis assessed the diagnostic accuracy of DUS in symptomatic PAD patients. We searched electronic databases for studies comparing DUS and arteriography. Arteries were analyzed individually and grouped into segments (aorto-common femoral, femoropopliteal, below the knee, and the entire lower limb). The meta-analysis estimated sensitivity, specificity, likelihood, and diagnostic odds ratios (DOR). Fifteen studies were included, analyzing 9,067 arteries. DUS accuracy for symptomatic PAD was 0.86 (95% CI 0.81-0.90) for sensitivity and 0.95 (95% CI 0.78-0.97) for specificity. The best results were observed for the femoropopliteal segment: sensitivity 0.86 (95% CI 0.80-0.90), specificity 0.95 (95% CI 0.93-0.97). The poorest performance was observed for the below-the-knee segment: sensitivity 0.78 (95% CI 0.60-0.89), specificity 0.92 (95% CI 0.78-0.97). Most studies had high and unclear risk of bias. There is significant heterogeneity in results, with a limited number of primary studies for each arterial segment, especially for the below-the-knee segment.